Science@iium - Wan Abdul Khodir, Wan Khartini; Abdul Hamid, Shafida; Meenakshi Sundram, Tamil Chelvan; Mohammad, Nurul Farahain; Abdullah, Mimi Hafizah; Razali, Azaima; Yusof, Fitri; Azizan, Nurhafizah; Muhsin, Amar (Kulliyyah of Science, 2018)
The Kulliyyah has spared no effort to assure that we provide the best tertiary education possible in pure and applied science. Our programmes are unique which include islamisation of knowledge that unifies science with religion. We are committed to providing our graduates with well-rooted knowledge, professional skills, qualities and attitudes that employers value most including logical and analytical thinking; and problem-solving. The moment students stepped in Kulliyyah of Science, is the beginning of a lifetime journey of learning exploration. Undoubtedly, this is the place where the great leaders of the future are nurtured